Pengaruh Berbagi Pengetahuan, Perilaku Kewarganegaraan Dalam Organisasi Dan Budaya Organisasi Terhadap Kinerja Guru SMAS Kurnia Puday Kabupaten Konawe - Marjani Marjani; Sabaruddin Sondeng; Fitriani Fitriani (Journal of Education and Teaching (JET), 2021)
This study aims to test and determine the effect of the relationship between variables. Data collection techniques used are observation, documentation and questionnaires, then processed by editing, tabulating, sorting, and interpreting. Liker scale and instrument validity and reliability tests were carried out for data measurement, to achieve the purpose of testing hypotheses, processed for analysis using multiple linear regression in order to determine the magnitude of the relationship and influence between variables. Statistical analysis of multiple linear regression on a sample of 30 people (teachers) was tested using the simultaneous test model (F test) and partial test (t test). The results of the study found that knowledge sharing, civic behavior in the organization and organizational culture simultaneously had a positive and significant effect on the performance of SMAS Kurnia Puday teachers.